1998
DOI: 10.1080/10473289.1998.10463758
|View full text |Cite
|
Sign up to set email alerts
|

VOC Recovery through Microwave Regeneration of Adsorbents: Process Design Studies

Abstract: Process design studies are described for a new type of VOC recovery system which uses microwave heating to regenerate adsorbents. Microwave regeneration systems create a highly concentrated effluent from which the VOCs can be recovered by condensation at near-ambient temperatures. Important design considerations, predicated on experimental work and model development, are identified and discussed. Parametric studies are then described that identify the optimal adsorbent selection, operating cycle, recovery conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…4, it is difficult to infer any effect of the flow regime on the residual oil levels since the gas flow appears to be mainly laminar, with some transition at the highest gas flow rate. The gas consumption rates required in this instance are over an order of magnitude lower than those reported by Price and Schmidt [29] for VOC desorption. This is thought to be due to the relatively high specific power used in this study, ∼250 W/g compared with the ∼2 W/g used in their work.…”
Section: Effects Of Nitrogen Flow Ratementioning
confidence: 60%
“…4, it is difficult to infer any effect of the flow regime on the residual oil levels since the gas flow appears to be mainly laminar, with some transition at the highest gas flow rate. The gas consumption rates required in this instance are over an order of magnitude lower than those reported by Price and Schmidt [29] for VOC desorption. This is thought to be due to the relatively high specific power used in this study, ∼250 W/g compared with the ∼2 W/g used in their work.…”
Section: Effects Of Nitrogen Flow Ratementioning
confidence: 60%
“…Another topic of investigation has been the microwave-induced regeneration of exhausted activated carbons. Thus, Price et al [58] and Cha et al [59] have reported microwave-assisted regeneration processes of activated carbon saturated with volatile organic compounds (VOC). As well as of carbons used in gas phase applications, the regeneration of activated carbons used in liquid phase adsorption has been studied.…”
mentioning
confidence: 99%
“…Although this method showed promising results in some applications (Stegmann and Hensel, 2004;Robers et al, 2004), it has to be taken into account that hot spots and electric discharges between the particles may occur. Thus, flammable adsorbents may be subject to spontaneous ignition in the presence of oxygen (Price and Schmidt, 1998).…”
Section: Process Optionsmentioning
confidence: 99%